2020
DOI: 10.7717/peerj.10328
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of lysophosphatidic acid metabolism in oral cancer promotes cell migration via the up-regulation of COX-2

Abstract: Oral squamous cell carcinoma (OSCC) is the sixth most common cancer worldwide and accounts for 300,000 new cases yearly. The five-year survival rate is approximately 50% and the major challenges to improving patient prognosis include late presentation, treatment resistance, second primary tumours and the lack of targeted therapies. Therefore, there is a compelling need to develop novel therapeutic strategies. In this study, we have examined the effect of lysophosphatidic acid (LPA) on OSCC cell migration, inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…ATX expression is amplified in various human carcinomas as well as in different cell types of the TME. [2][3][4][5] Our initial observation that p53-KO mice have elevated Enpp2 expression prompted us to investigate if p53 can regulate the transcription of Enpp2 expression. 40 In the present study, we showed that MEF derived from p53-KO or p53 R172H mice indeed express more ATX than MEF derived from WT mice, suggesting that WT p53 represses Enpp2 transcription.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ATX expression is amplified in various human carcinomas as well as in different cell types of the TME. [2][3][4][5] Our initial observation that p53-KO mice have elevated Enpp2 expression prompted us to investigate if p53 can regulate the transcription of Enpp2 expression. 40 In the present study, we showed that MEF derived from p53-KO or p53 R172H mice indeed express more ATX than MEF derived from WT mice, suggesting that WT p53 represses Enpp2 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…ATX expression is amplified in various human carcinomas as well as in different cell types of the TME 2–5 . Our initial observation that p53‐KO mice have elevated Enpp2 expression prompted us to investigate if p53 can regulate the transcription of Enpp2 expression 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PI3K/AKT signalling seems to be at the epicentre of LPA pro-tumourigenic actions, as it has also been suggested to drive LPA-induced proliferation and migration in oesophageal squamous cell carcinoma [103]. LPP1/3 expression is downregulated in oral cancer, whereas ATX displays high expression, and ATX-synthesised LPA subsequently induces cyclooxygenase-2 (COX-2) mRNA expression to promote cell migration [104].…”
Section: Lpa In Other Tumour Typesmentioning
confidence: 99%
“…We have mentioned the idea of treating of related diseases by blocking ATX-LPA axis above. Recently, many studies have shown that inhibiting ATX can have a promising therapeutic effect on many diseases, such as the growth and metastasis of various tumors such as oral squamous cell carcinoma (OSCC) [31] and breast cancer [32], peritoneal spread in patients with pancreatic ductal adenocarcinoma (PDAC) [33], cardiovascular disease [34], fibrosis of organs such as kidney, heart and lung [35,36], and central nervous system disease [37,38]. It has been shown that ATX is essential for the development of embryos.…”
Section: The Potential Of Atx As a Drug Targetmentioning
confidence: 99%